Analisis Strategi Pengembangan Usaha Bolu Kemojo Usaha Bunda Pelintung - Musdiana, Andi Desy; Aditiya, Variza; Hartutik, Dwi; Suherman (Jurnal Administrasi Publik dan Bisnis, 2024)
Bolu Kemojo is one of the traditional foods typical of Riau Province that still survives amidst changes in the tastes of modern society. This study aims to analyze the business development strategy of Bolu Kemojo carried out by Usaha Bunda Pelintung located in Dumai City. This study uses a qualitative descriptive method with a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach to determine the strengths, weaknesses, opportunities, and threats faced by this business. The results of this study indicate that market development strategies and product innovation are the right steps to increase business competitiveness amidst increasingly tight competition.